Pendampingan Pengelolaan Di Lembaga Diniyah Islamiyah Adam Institute Dusun Numpeng – Desa Jago Kecamatan Praya Lombok Tengah - Muh. Asroruddin Al Jumhuri; Fatmawati, Fatmawati (STAI Al-Amin Gersik Kediri Lombok Barat-NTB, 2023)
Historically, the birth of madrasah in Indonesia can be seen from two aspects. First, the internal aspect of Islamic teachings prioritizes the obligation to study, including religious knowledge. Second, the external factor is the condition of Islamic education in Indonesia which requires the presence of madrasah as an alternative religious education during modern Dutch colonial educational institutions in Indonesia. Researchers have conducted mentoring activities for managing institutions at the Madrasah Diniyah Islamiyah Adam Institute, Numpeng Hamlet, Jago Village, Praya District. This guidance is focused on the management of teaching staff at the Madrasah. The form of mentoring activities is carried out by being directly involved in the direction of the Madrasah Diniyah Islamiyah Adam Institute, Numpeng Hamlet, Jago Village, Praya District, Central Lombok. Namely, apply yourself in planning, monitoring, and evaluating every activity at Madrasah Diniyah Islamiyah Adam Institute. It is intended that every action and plan be carried out in accordance with what was previously planned by the Head of Madrasah Diniyah Islamiyah Adam Institute and all administrators and teachers.